Corrosion Resistance and Cytotoxicity of Copper-Based and Nickel-Chromium Alloys for Cast Post and Core Fabrication - Mina Mohaghegh; Mohammad Kazemi; Mehdi Bidaki; Mitra Farzin (Frontiers in Dentistry)
Objectives: This study assessed the corrosion resistance and cytotoxicity of two copper-based alloys and one nickel-chromium (Ni-Cr) alloy used for post and core fabrication.